Perlindungan Terhadap Tenaga Kesehatan di Masa Adaptasi Kebiasaan Baru Selama Pandemi Covid-19 - patandianan, alan crispapanrio (Nommensen Journal of Medicine, 2021)
Background: The spread of the Covid-19 disease that occurred at the end of 2019 had many impacts on society, including health workers. Therefore, efforts to protect against the dangers of Covid-19 are needed in the workplace so that the safety and health of workers is guaranteed. The application of a hierarchy of hazard control is an example of a method that can be applied. Goal: To determine the application of methods of protecting health workers in the adaptation period for new habits during the Covid-19 pandemic. Method: The making of a Literature Review was carried out with a literature review with a descriptive approach based on relevant research articles or journals. Search scientific literature on PubMed electronic database using the keyword "(" Covid-19 ") AND (" HCW "OR" Healthcare Worker ") AND (" Protection "). The inclusion criteria used were articles with a publication time span from March to September 2020, articles in Indonesian and English which were full text. The exclusion criteria used were articles that were not related to the theme of the literature review. Result: Based on the 9 reviewed literature, it was found that the protection measures currently implemented in each workplace were still in the less optimal category, this was because there were still many problems, one of which was the insufficient availability of PPE. The problem of lack of availability of PPE is a problem that must be resolved, so that health workers can work safely and comfortably. Conclusion: Workforce protection efforts mostly lead to the use of PPE, but from several studies that the availability of PPE is still a major problem in maximizing protection efforts from the dangers of Covid-19.